Bridging Quranic Epistemology and Outcome-Based Education: Digital Storytelling Pedagogy in Pesantren - Taufikin Taufikin; Fajar Syarif; Muh. Ubaidillah Alghifary Slamet; Ahmad Hariyadi; Ahmad Falah; Moses Adeleke Adeoye (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
Outcome-Based Education (OBE) has increasingly been criticized for overemphasizing measurable competencies and technical achievements, neglecting ethical, spiritual, and philosophical dimensions of learning. Thus, pesantren offers an educational paradigm that integrates knowledge formation with moral and spiritual values in Islamic teachings. This study examines how the concept of Iqra’ (Q.S. al-‘Alaq [96]: 1-5 is contextualized within OBE framework by implementing digital storytelling pedagogy in pesantren. It employs a qualitative case study approach, combining in-depth interviews, participatory observation, and content analysis of short films produced by Islamic boarding school students and disseminated through digital platforms. It investigates how audiovisual narratives interpret, transform, and communicate Quranic values in contemporary learning. The findings reveal that digital storytelling projects reflect interconnected dimensions. First, the ontological dimension emphasizes the understanding of revelation as the foundation of knowledge and human consciousness. Second, the epistemological dimension is manifested in reading, interpreting, contextualizing, and transforming Quranic messages into creative audiovisual narratives. Third, ethical and moral values dissemination to wider audiences reflects an axiological dimension through digital media. These strengthen Quranic literacy and cultivate key OBE competencies (critical thinking, creativity, collaboration, communication, and digital literacy). This study significantly contributes to the Islamic education and contemporary pedagogy discourse. It proposes a conceptual framework bridging Quranic epistemology with OBE. It also demonstrates digital storytelling as a transformative pedagogical approach integrating spiritual formation with 21st-century competencies. Furthermore, it positions pesantren as an adaptive and innovative educational institution capable of harmonizing religious tradition, digital technology, and holistic learning in the contemporary digital era.